2007
DOI: 10.1002/aqc.838
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic impacts on spatial and temporal distribution of Corbicula fluminea (Müller, 1774) in the River Minho estuary, Portugal

Abstract: ABSTRACT1. The non-indigenous species Corbicula fluminea (Mu¨ller, 1774) is one of the most invasive bivalves in freshwater ecosystems. This Asian clam was first reported in the River Minho estuary in 1989. After a short period of time, it became the major component of the local benthic fauna in terms of abundance and biomass.2. In the autumn of 2004 and 2005, spatial and temporal variations in abundance, biomass and population structure of C. fluminea were investigated at 16 sites in the freshwater subtidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
3
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 38 publications
2
67
3
9
Order By: Relevance
“…The coarse and very fine sediment fractions, the high water temperature and the low benthic organic matter content in very fine fraction of sediment provided suitable habitat for C. fluminea and resulted in high biomass values. These results are in accordance with previous studies, which demonstrated that C. fluminea reached its maximum abundance at sites with coarse and find sand, or small gravel sized substrate (McMahon 1983;Belanger et al 1991;Bagatini et al 2007;Sousa et al 2008c).…”
Section: Discussionsupporting
confidence: 93%
“…The coarse and very fine sediment fractions, the high water temperature and the low benthic organic matter content in very fine fraction of sediment provided suitable habitat for C. fluminea and resulted in high biomass values. These results are in accordance with previous studies, which demonstrated that C. fluminea reached its maximum abundance at sites with coarse and find sand, or small gravel sized substrate (McMahon 1983;Belanger et al 1991;Bagatini et al 2007;Sousa et al 2008c).…”
Section: Discussionsupporting
confidence: 93%
“…Applying such findings to our results it was also possible that the higher river flows during 2009/2010 resulted in higher mortalities, negatively affecting bivalve populations and possibly imposing a serious threat to some species. C. fluminea, has a typical opportunistic life cycle (Sousa et al, 2008b(Sousa et al, , 2008d giving this species an advantage over the four native species concerning extreme climatic events, since it recovers more rapidly (Sousa et al, 2008a(Sousa et al, , 2008cIlarri et al, 2011). Extreme events are predicted to increase over the next few decades as a result of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerate low water temperatures and prefer sandier sediments mixed with silt and clay (which enhance the organic matter content). However, in some ecosystems this species can be found in all types of sediments (with or without submerged vegetation) (Sousa et al 2008) (6) sediments. At the same time, there is growing evidence that bivalves also excrete large amounts of inorganic nutrients, mainly inorganic nitrogen, at the form of faeces and pseudofaeces (Asmus & Asmus 1991).…”
Section: Possible Ecological Effectsmentioning
confidence: 99%
“…This occurrence can abruptly cause massive mortalities in all the benthic fauna, also affecting the water quality. Usually, the C. fluminea population rapidly recovers reaching previous abundance and distribution while native species usually take a long time to react (Sousa et al 2007b(Sousa et al , 2008. Therefore, this phenomenon could act in favour of C. fluminea and against native species, and may determine and/or accelerate the extirpation of some native species.…”
Section: Possible Ecological Effectsmentioning
confidence: 99%
See 1 more Smart Citation